71 Contributing Factors to Hypertension in Rural Area: Study of Knowledge, Attitude, and Behaviour Among Health Care Providers and Patients. (November 2017) - Fredy, Felix Chikita; Felicia, Devi; Rahayu, Sarah Febiana; Gabriella, Alexandra; Proklamartina, Nurnajmia Curie; Mulyadi, Joshua Patrick; Andriyati, Ratna; Nugroho, Bhayu Hanggadhi; Lilihata, Gracia; Kane, Vincent; Pravian, Dexanda; Soenarta, Arieska Ann
Abstract : Introduction: Based on Indonesia Basic Health Survey 2013, one of four people suffers from hypertension. The trends nowadays shows an incremental prevalence of hypertension in rural area (urban vs rural; 14.2% vs 13.9% in 2004, 30.8% vs 32.2% in 2007, and 26.1% vs 25.5% in 2013). Regarding this issue, it is a need to look for factors that contribute to its incidence in rural area. Lack of knowledge, attitude, and behaviour (KAB) regarding hypertensioncould be one of the important contributing factors. There is no study before assessing status of KAB of health care providers and patientsregarding hypertension in rural and remote area. Objectives: To assess the status of KAB of health care providers and the patients in primary health care (PHC) at rural and remote area in Indonesia regarding hypertension. Methods: The present cross-sectional study was carried out in 8 PHC spread in 7 provinces in Indonesia. Subjects were hypertensive patients and health care providers, including general practitioners (GP), nurses, specialists. The data were collected from subjects using comprehensive questionnaire guided by interviewers. All available health care providers and patients in PHC centres were approached to determine their KAB regarding hypertension. Questionnaires were validated and pilot tested. Each section of the questionnaire was scored and the total scores ranged 0.0–100.0 points were calculated. KAB status of health care providers and patients based on the same items in questionnaires was compared. Results: A total of 185 health care providers (42.7% males; median age 28yo), consisted of 68 GP, 107 nurses, 10 specialists, and 184 patients with hypertension (41.8% males; median age 56yo) were enrolled in the study. Most of patients showed poor knowledge (70.7%), average attitude (53.8%), and neutral behaviour (51.6%), while health care providers also showed almost same level: average knowledge (54.6%), average attitude (65.4%), and neutral behaviour (56.8%). Patients' knowledge score was influenced by the presence of family history of hypertension (p = 0.002), previous information from health care providers ( p = 0.002 ), and educational background ( p < 0.001 ). Health care providers was the most common source of information reported by 113 (61.4%) subjects, yet only 12 (6.5%) subjects admitted ever got information adequately. While for GP, experience of attending any hypertension conferences/seminar ( p = 0.05) and the origin of province ( p = 0.009) were two factors significantly associated with GPs' level of knowledge. For same items in questionnaire, health care providers showed better score inknowledge (50.8 ± 23.0vs 28.4 ± 19.0; p < 0.001 ) and behaviour (60.1 ± 18.5 vs 44.0 ± 23.2; p < 0.001 ), but no significant difference found in attitude (38.9 ± 30.1 vs33.0 ± 25.8; p = 0.08 ). Conclusion: The study revealed that KAB of patients in PHC in rural and remote areawas low. It also was noted that the health care providers, the main source of hypertention information, were also lacked of KAB. Hypertension education must be strengthened for both health care providers and patients. An increased KAB is crucial for successful management of hypertension in Indonesia.